PENGEMBANGAN PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN BERBASIS "GREEN CONSTITUTION" UNTUK MENUMBUHKAN KEADABAN KEWARGANEGARAAN TERHADAP LINGKUNGAN - Susan Fitriasari, - (2017)
This study aims to know the development of citizens' virtue through Civic Education learning model based Green Constitution in West Java High School. This research used qualitative and quantitative approach with R&D design (Research and Development). Data collecting techniques by questionnaire, observation, documentation study and literature study. The population in this study were high school students in West Java with a sample of 314 students divided into 159 control class students and 155 students of experimental class. The results showed that: 1) The initial description of high school students virtue related to the knowledge and attitude of virtue between the control and the experimental class has not shown optimal results. Similarly, the initial description of Civic Education learning in the control and experimental classes has not shown the participatory learning process towards environment; 2) The planning of Civic Education learning based Green Constitution is done together with teacher and researcher through focus group discussion by making Lesson Plan which contains learning component as a whole, among others: learning objectives, Civic Education learning materials based green constitution; and sources/media that are integrative, collaborative, and comprehensive; 3) The implementation Civic Education learning based green constitution includes initial activities, core activities, and closing activities. The procedures are brainstorming, introducing environmental law materials, identifying environmental issues, selecting problems for classroom studies, gathering information and documentation, establishing class portfolio, portfolio displays, and reflecting on learning experiences; 4) Authentic assessment becomes the basis measuring of the Civic Education learning based green constitution include: attitude assessment, knowledge assessment with written test and oral test, and portfolio assessment through process assessment, product assessment, and performance appraisal; 5) The effectiveness of Civic Education learning based green constitution has a significant positive effect on the development of students virtue. The conclusion is the model was assumed for fostering civic virtue both theoretically and practically. Civic Education learning based green constitution invites student closer to the problems that occur in society and to make alternative policy for every environmental issu. Penelitian ini bertujuan untuk mengetahui pengembangan keadaban warga negara melalui model pembelajaran PKn berbasis Green Constitution di Sekolah Menengah Atas Jawa Barat. Penelitian ini menggunakan pendekatan kualitatif dan kuntitatif desain R&D (Research and Development). Teknik pengumpulan data dilakukan dengan angket, observasi, studi dokumentasi dan studi literatur. Populasi dalam penelitian ini adalah siswa SMA di Jawa Barat dengan sampel sebanyak 314 orang yang terbagi ke dalam 159 siswa kelas kontrol dan 155 siswa kelas eksperimen. Hasil penelitian menunjukkan bahwa: 1) Gambaran awal Keadaban Kewarganegaraan pada siswa SMA berkaitan dengan pengetahuan dan sikap keadaban antara kelas kontrol dan kelas eksperimen belum menunjukkan hasil yang optimal. Begitu pula gambaran awal pembelajaran PKn di kelas kontrol dan eksperimen pun belum menunjukkan proses pembelajaran partisipasif terhadap lingkungan; 2) Pembelajaran PKn berbasis green constitution dilakukan perencanaan bersama guru dan peneliti melalui focus group discussion dengan membuat Rencana Pelaksanaan Pembelajaran yang berisi komponen-komponen pembelajaran secara utuh di antaranya : tujuan pembelajaran, materi pembelajaran PKn berbasis green constitution; dan sumber/media yang bersifat integratif, kolaboratif, dan komprehensif; 3) Pelaksanaan pembelajaran PKn berbasis green constitution mencakup kegiatan awal, kegiatan inti, maupun kegiatan penutup. Prosedur yang dilaksanakan adalah brainstorming/penggalian masalah lingkungan, pengenalan materi hukum lingkungan, mengidentifikasi masalah lingkungan, memilih masalah untuk kajian kelas, mengumpulkan informasi dan dokumentasi, membentuk portofolio kelas, menampilkan portofolio, dan merefleksi pengalaman belajar; 4) Penilaian autentik menjadi dasar pengukuran pembelajaran PKn berbasis green constitution yang meliputi : penilaian aspek sikap, penilaian pengetahuan berupa tes tulis dan tes lisan, dan penilaian portofolio melalui penilaian proses, penilaian produk, dan penilaian performance; 5) Efektifitas pembelajaran PKn berbasis green constitution berpengaruh positif signifikan terhadap pengembangan Keadaban Kewarganegaraan siswa. Kesimpulannya bahwa model ini dapat mengembangkan Keadaban Kewarganegaraan baik secara teoritis maupun praktis. Pembelajaran PKn berbasis green constitution mengajak siswa lebih dekat dengan masalah-masalah yang terjadi di lingkungan masyarakat dan mengambil keputusan kebijakan alternatif untuk setiap permasalahan lingkungan.----